Pelatihan Aplikasi Perangkat Lunak Multisim Pada Laboratorium Jurusan Kelistrikan SMK Swa Bina Karya - Indra Roza; Yussa Ananda; Lisa Adriana Siregar; Agus Almi Nasution; Ahmad Yanie (LPPM STIKOM Tunas Bangsa, 2021)
Multisim software application training at vocational schools is one way to introduce a software that functions to facilitate lessons related to electricity both in theory and practice. The theory learned in class can be applied to various basics of electronics and electrical circuits related to testing and practice so that vocational students can develop basic knowledge of electronics and electricity. while for the laboratory it can be used for calculations with existing circuit measurements in modules and in theory. By introducing this tool, it is hoped that vocational students can form study groups in schools so that learning outcomes in class and practice can be achieved..